REDUPLIKASI DALAM BAHASA ANGKOLA MANDAILING - Syaifuddin Zuhri Harahap (Balai Bahasa Sumatera Utara, 2018)
The purpose of this study was to examine reduplication in Angkola Mandailing language using the Theory of Generative Morphology related to reduplication suggested by Simatupang (1983) and supported by Ramlan (2001) and Chaer (2008). The data for this study were a number of morphemes in Angkola Mandailing language containing the element of reduplication. The oral data were obtained from various conversations occured in the Angkola Mandailing community and several informants, while the written data were obtained from the literatures written in Angkola Mandailng language, dictitonary and scientific writtings discussing about Angkola Mandailing language. The result of this study showed that the types of reduplication in Angkola Mandailing language are as follows. First, twowenteen types of reduplication are found in Angkola Mandailing language. Second, the contexstually it is found the meaning of these types of reduplication Independent Context and Dependent Context in the Angkola Mandailing language.